The Transfer Learning Task as the Means of Metalearning Tasks Solution - Savchenko, Ye.A.; Savchenko, M.Yu. (Control systems & computers, 2020)
The methods for solving the problems of transfer learning are reviewed from the point of view of solving the metalearning tasks. The concepts of metalearning, transfer learning, multi-task learning, inductive transfer and lifelong learning are given. A scheme for solving the metalearning problem using the inductive approach is proposed. Metalearning is a generalization of all previously solved problems. It gives a possibility to save resources and to use the existing experience in solving learning problems in an optimal way.